Ferrocene derivatives with planar chirality and their enantioseparation by liquid‐phase techniques. Issue 1 (4th September 2022) - Peluso, Paola; Mamane, Victor
Abstract: In the last decade, planar chiral ferrocenes have attracted a growing interest in several fields, particularly in asymmetric catalysis, medicinal chemistry, chiroptical spectroscopy and electrochemistry. In this frame, the access to pure or enriched enantiomers of planar chiral ferrocenes has become essential, relying on the availability of efficient asymmetric synthesis procedures and enantioseparation methods. Despite this, in enantioseparation science, these metallocenes were not comprehensively explored, and very few systematic analytical studies were reported in this field so far. On the other hand, enantioselective high‐performance liquid chromatography has been frequently used by organic and organometallic chemists in order to measure the enantiomeric purity of planar chiral ferrocenes prepared by asymmetric synthesis. On these bases, this review aims to provide the reader with a comprehensive overview on the enantioseparation of planar chiral ferrocenes by discussing liquid‐phase enantioseparation methods developed over time, integrating this main topic with the most relevant aspects of ferrocene chemistry. Thus, the main structural features of ferrocenes and the methods to model this class of metallocenes will be briefly summarized. In addition, planar chiral ferrocenes of applicative interest as well as the limits of asymmetric synthesis for the preparation of some classes of planar chiral ferrocenes will also be discussed with the aim to orient analytical scientists towards 'hot topics' and issues which are still open for accessing enantiomers of ferrocenes featured by planar chirality.